The Concept of Gharimin in Contemporary Fiqh: A Comparative Analysis of Yusuf al-Qaradawi and Wahbah al-Zuhayli - Nst, Andri Muda; Hamid, Asrul; Ritonga, Raja; Hsb, Zuhdi; Akhyar, Akhyar (Institut Agama Islam Negeri Kendari, 2025)
This research explores the concept of gharimin in contemporary fiqh by analyzing the views of Yusuf al-Qaradawi and Wahbah al-Zuhaili. Gharimin refers to individuals in debt who are unable to repay it, as stated in QS. At-Taubah/9:60, making them one of the eight categories (asnaf) eligible to receive zakat. In modern times, the definition of gharimin has expanded in line with increasingly complex social and economic challenges. Yusuf al-Qaradawi adopts a more flexible and contextual approach, viewing zakat as an instrument of empowerment for those in debt due to urgent needs, economic crises, or other social pressures. On the other hand, Wahbah al-Zuhaili maintains a stricter classical fiqh perspective, emphasizing that only debts valid under Sharia law qualify, with a focus on preventing zakat misuse. The study applies a qualitative method using library research to examine both primary and secondary sources related to gharimin and its application in modern zakat management. The findings reveal contrasting methodologies: al-Qaradawi’s contextual and adaptive approach versus al-Zuhaili’s normative and rigorous stance. The research highlights the need for a balanced strategy in managing zakat for gharimin, combining legal compliance with adaptability to current socio-economic realities. Such a balance is essential for effectively addressing poverty and promoting economic stability within the Muslim community. This study contributes to the discourse on contemporary Islamic law by offering practical insights into zakat distribution, particularly in navigating the tensions between traditional principles and modern challenges.